Influence of shape on the optical properties of hematite aerosol. Issue 14 (23rd July 2015) - Veghte, Daniel P.; Moore, Justin E.; Jensen, Lasse; Freedman, Miriam Arak
Abstract Mineral dust particles are the second highest emitted aerosol type by mass. Due to changes in particle size, composition, and shape that are caused by physical processes and reactive chemistry, optical properties vary during transport, contributing uncertainty in the calculation of radiative forcing. Hematite is the major absorbing species of mineral dust. In this study, we analyzed the extinction cross sections of nigrosin and hematite particles using cavity ring‐down aerosol extinction spectroscopy (CRD‐AES) and have measured particle shape and size distributions using transmission electron microscopy. Nigrosin was also used in this study as a spherical standard for absorbing particles. The size‐selected nigrosin particles have a narrow size distribution, with extinction cross sections that are described by Mie theory. In contrast, the size distribution of size‐selected hematite particles is more polydisperse. The extinction cross sections were modeled using Mie theory and the discrete dipole approximation (DDA). The DDA was used to model more complex shapes that account for the surface roughness and particle geometry. Of the four models used, Mie theory was the simplest to implement, but had significant error with a 26.1% difference from the CRD‐AES results. By increasing the complexity of the models using the DDA, we determined that spheroids had a 14.7% difference, roughened spheres a 12.8% difference, and roughened spheroids a 11.2% difference from the experimental results. Using additional parameters that account for particle shape is necessary to model the optical properties of hematite particles and leads to improved extinction cross sections for modeling aerosol optical properties.